Novel Siglec-15-Sia axis inhibitor leads to colorectal cancer cell death by targeting miR-6715b-3p and oncogenes - Ahmad, Mohammed Saqif; Braoudaki, Maria; Patel, Hershna; Ahmad, Irshad; Shagufta,; Siddiqui, Shoib Sarwar (Frontiers in Immunology, 2023)
Siglecs are well known immunotherapeutic targets in cancer. Current checkpoint inhibitors have exhibited limited efficacy, prompting a need for novel therapeutics for targets such as Siglec-15. Presently, small molecule inhibitors targeting Siglec-15 are not explored alongside characterised regulatory mechanisms involving microRNAs in CRC progression. Therefore, a small molecule inhibitor to target Siglec-15 was elucidated in vitro and microRNA mediated inhibitor effects were investigated. Our research findings demonstrated that the SHG-8 molecule exerted significant cytotoxicity on cell viability, migration, and colony formation, with an IC50 value of approximately 20µM. SHG-8 exposure induced late apoptosis in vitro in SW480 CRC cells.. Notably, miR-6715b-3p was the most upregulated miRNA in high-throughput sequencing, which was also validated via RT-qPCR. MiR-6715b-3p may regulate PTTG1IP, a potential oncogene which was validated via RT-qPCR and in silico analysis. Additionally, molecular docking studies revealed SHG-8 interactions with the Siglec-15 binding pocket with the binding affinity of -5.4 kcal/mol, highlighting its role as a small molecule inhibitor. Importantly, Siglec-15 and PD-L1 are expressed on mutually exclusive cancer cell populations, suggesting the potential for combination therapies with PD-L1 antagonists.